Sprint Express : bulletin de la Fédération Sportive Gaie et Lesbienne CGPIF. (Paris : Fédération CGPIF, 1996)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie: BP 120, 75623 Paris Cedex 13
Frans
Periodiek